Anthropocentrism and the Ecological Crisis: An Analysis of Laudato Si’ on the Church’s Role in Public Policy Transformation - Losianus Harjon (Politeknik Siber Cerdika Internasional, 2026)
Background: The ecological crisis has emerged as one of the most urgent global challenges, driven largely by anthropocentric paradigms that legitimize the exploitation of nature for economic and technological interests. Objective: This study aims to analyze the ecological crisis through an ecotheological interpretation of Laudato Si' and to examine the Church’s prophetic role in transforming ecological public policy. Method: This research employs a qualitative literature-based design using a hermeneutic-ecotheological approach. Primary data were obtained from Laudato Si’, while secondary sources included ecotheological literature, Catholic Social Teaching, environmental ethics, and public policy studies. Data were analyzed through textual interpretation, thematic categorization, and conceptual synthesis. Findings and Implications: The findings reveal that anthropocentrism contributes to deforestation, climate change, pollution, biodiversity loss, habitat destruction, and social inequality. Ecological degradation also fosters spiritual alienation and weakens human responsibility toward creation. The Church’s prophetic mission is reflected in ecological advocacy, environmental education, ethical criticism of exploitative development, and participation in policy discourse based on integral ecology. These findings suggest that ecological ethics can provide a normative basis for sustainable and socially responsible public policies. Conclusion: The ecological crisis represents an environmental, social, and moral challenge that requires a transformation of values and policies. Integral ecology offers a comprehensive framework for promoting sustainability, environmental justice, and the common good through collaborative action among religious institutions, governments, and society.